1981
DOI: 10.3354/meps005069
|View full text |Cite
|
Sign up to set email alerts
|

Gregarious Settlement by the Larvae of Hydroides dianthus (Polychaeta: Serpulidae)

Abstract: Larval development of the serpulid polychaete worm, Hydroides dlanthus Verrill 1893 parallels that of other closely related species. The larvae prefer to settle upon surfaces already inhabited by other members of their own species rather than to colonize surfaces without such conspecific residents. However, very wide variations in the intensity of settlement are observed. These differences in the amount of settlement cannot presently be attributed to any single variable. Gregarious settlement appears to be typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 4 publications
1
43
0
Order By: Relevance
“…Jackson 1977b, Scheltema et al 1981, Schmidt 1983 (Keough 1984). There are other examples in which solitary animals have been shown to be superior interference spatial competitors: Castric (1974) reported that Pomatoceros triqueterwas capable of overgrowing thinly encrusting bryozoans, and E. Voigt (pers.…”
Section: Discussionmentioning
confidence: 99%
“…Jackson 1977b, Scheltema et al 1981, Schmidt 1983 (Keough 1984). There are other examples in which solitary animals have been shown to be superior interference spatial competitors: Castric (1974) reported that Pomatoceros triqueterwas capable of overgrowing thinly encrusting bryozoans, and E. Voigt (pers.…”
Section: Discussionmentioning
confidence: 99%
“…Settlement occurs only on biofilmed surfaces, but gregarious settlement additionally requires the presence of water-soluble chemical cues associated with bodies of live conspecifics (Toonen 1993, Toonen & Pawlik 1996. Larvae are approximately 300 µm long at competency, and undergo rapid and obvious morphological changes during metamorphosis that distinguish settled individuals from attached larvae (Scheltema et al 1981, Carpizo-Ituarte & Hadfield 1998.…”
Section: Introductionmentioning
confidence: 99%
“…We address several questions in this manuscript. First, although H. dianthus has been shown to exhibit gregarious settlement in the laboratory (Scheltema et al 1981, Toonen & Pawlik 1996, is this species actually aggregated in the field? This is an important point to consider, because patterns of gregarious larval settlement in the laboratory are likely to have little biological relevance if conspecifics do not show an aggregated dispersion in the field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, multiple taxa may respond to conspecific cues. For example, 4 gregariousness has been reported for some taxa (oysters, Crisp, 1967;Bayne, 1969;polychaetes, 5 Knight-Jones, 1951;Scheltema et al, 1981). Second, larval settlement behavior may mediate the 6 distribution and timing of settlement.…”
mentioning
confidence: 99%